A brief cognitive-behavioural intervention for pain reduces secondary hyperalgesia - Salomons, Tim V.; Moayedi, Massieh; Erpelding, Nathalie; Davis, Karen D. (Pain (Amsterdam), 2014)
A brief cognitive behavioural intervention reduces pain unpleasantness and secondary hyperalgesia elicited by repeated nociceptive thermal stimuli. Repeated exposure to pain can result in sensitization of the central nervous system, enhancing subsequent pain and potentially leading to chronicity. The ability to reverse this sensitization in a top-down manner would be of tremendous clinical benefit, but the degree that this can be accomplished volitionally remains unknown. Here we investigated whether a brief (∼5min) cognitive-behavioural intervention could modify pain perception and reduce central sensitization (as reflected by secondary hyperalgesia). In each of 8 sessions, 2 groups of healthy human subjects received a series of painful thermal stimuli that resulted in secondary hyperalgesia. One group (regulate) was given brief pain-focused cognitive training at each session, while the other group (control) received a non-pain-focused intervention. The intervention selectively reduced pain unpleasantness but not pain intensity in the regulate group. Furthermore, secondary hyperalgesia was significantly reduced in the regulate group compared with the control group. Reduction in secondary hyperalgesia was associated with reduced pain catastrophizing, suggesting that changes in central sensitization are related to changes in pain-related cognitions. Thus, we demonstrate that central sensitization can be modified volitionally by altering pain-related thoughts.